PENDAMPINGAN PEMBELAJARAN PIDATO DENGAN METODE PRACTICE REHEARSAL PAIRS PADA SISWA MADRASAH IBTIDAIYAH - Hardiana, Maulidia Tifani Alfin Nur; Aisah, Siti; Anggraini, Yussi (Faculty of Cultural Studies, Universitas Brawijaya, 2022)
Speech is one of the skills that must be practiced by students in elementary school. Speech is one of the first steps to practice oral communication skills. The fact that occurs in the classroom that students feel less able to do this activity. In addition, students feel that their level of self-convidence is very low. In this regard, the researchers provided assistance to students to practice speech activities using the practice rehearsal pairs method. This activity was carried out at MI Mafatihul Huda. The method of implementation includes preparation, implementation of activities, evaluation, and preparation of final report. As for the result of the activites, the students confidence in giving speeches in pairs. In addition, speech practice is able to hone students speaking skills and increase students interest in learning because they study in pairs with their friends.